Perceived Project Climate and Project commitment - Al Marzouqi, Mohammed Abdulrahman (2011)
This research paper explores the relationship between project climate and project commitment in the context of UAE government sector. The purpose of this study is to identify the main factors that influence the commitment of individuals' towards their project and test in the correlation between those factors and project commitment. Through extensive review of literatures five factors of project climate were identified; strategic alignment, project procurement, organisational structure, leadership and project teamwork. In order to carry on this study a questionnaire was developed and distributed to more than 40 government organisations in the Emirate of Abu Dhabi. Based on 659 responses the data was analysed using statistics program (SPSS). The results revealed that project climate is significantly related to project commitment. In addition, based on the statistical evidence all identified factors were found to be significantly related to project commitment, except the organisational structure factor which was unexpectedly not related to the project commitment. The positive relationship did not take place for organisational structure factor probably due to low reliability figure accounted for the total items of this factor. Finally, some actionable recommendations were proposed for the government organisations in UAE to enhance people commitment towards their project and achieve project success. An example of the recommendation is that, projects in the government organisations should have high strategic focus and the strategic direction must be clearly determined before selection of individual project in order to link the project objective with the organisation strategy.